Maribor med obema vojnama in vprašanje vojaške infrastrukture - Kladnik, Tomaž (Studia Historica Slovenica, 2021)
Basing on the research of archival sources and newspapers, the article discusses the urban development of the city of Maribor from the perspective of construction and change of use of the existing military infrastructure, its influence on the city’s development and its economic and everyday life in the period between the both world wars. For seventy years after the construction of the Southern Railway (1846), Maribor had been in the centre of traffic routes in the empire. Since one of the biggest military infrastructures in this part of Austria-Hungary was situated in Maribor, the city also had an important military-strategic position. With the downfall of Austria-Hungary and the creation of a new State of Slovenes, Croats and Serbs, the geostrategic position of Maribor changed considerably. Nev- ertheless, with its position and military infrastructure density, it preserved its important military role even in the new state. The discussed period in the city was thus marked by negotiations between the civil and military administration considering the ownership of the military infrastructure and the paying of its rent.
Keywords: armed forces; Država Slovencev, Hrvatov in Srbov; economic development; gospodarski razvoj; Kingdom of Serbs Croats and Slovenes; Kingdom of Yugoslavia; Kraljevina Jugoslavija; Kraljevina Srbov, Hrvatov in Slovencev; Maribor; military infrastructure; military life; Slovene terrotory; State of Slovenes, Croats and Sebs; vojaška zgodovina; vojaški objekti; vojaško življenje; vojska